Biochar-compost amendment enhanced sorghum growth and yield by improving soil physicochemical properties and shifting soil bacterial community in a coastal soil - Yin, Shaojing; Suo, Fengyue; Zheng, Ying; You, Xiangwei; Li, Hui; Wang, Juying; Zhang, Chengsheng; Li, Yiqiang; Cheng, Yadong (Frontiers in Environmental Science, 2022)
Soil salinization, an important type of soil degradation, has become a problem restricting crop production and food quality. The remediation technologies by using compost and biochar were considered sustainable and environmentally friendly; but the sole application of compost or biochar hardly get the satisfactory remediation effects. Until now, information about the effects of co-composted biochar on soils are limited, especially in the coastal soil. This study investigated the impact and potential underlying mechanism of corn straw biochar (BC), seaweed compost (SC), and co-composted BC and SC (BCSC) on the growth and yield of sorghum (Sorghum bicolor (L.) Moench) in the coastal soil of China in a pot experiment. BC and BCSC treatments increased dry biomass and yield of the sorghum by 44.0-52.4% and 132.9-192.3%, respectively. Similarly, the root morphologies of sorghum, including surface area and average diameter, were also increased with BC and BCSC addition. Meanwhile, BCSC treatment showed a better performance than the others did. The enhanced growth and yield of sorghum was primarily resulted from the improvement of soil properties (WHC, SOM, and EC) and nutrient availability (Olsen-P and AK content). In addition, the increased diversity and shifted composition of soil bacteria with the BC and BCSC addition might also account for the increased growth and yield of sorghum. Furthermore, the enhanced relative abundances of beneficial bacteria Vicinamibacteraceae (39.0%) and Sphingomonadaceae (41.5%) in the rhizosphere soil were positively correlated with the content of available nutrients (NH4+, Olsen P, and available K) in the coastal soil, which might reveal the mechanism of enhancing growth under the established collaborative interactions of them. Our study provides the potential of using biochar-compost to ameliorate the degradation of coastal soils and improve crop yield.